Sexual abuse of children: an update. - Finkel, K C (1987)
An increasing number of studies in the past decade have shown that sexual abuse of children is disturbingly common. The author reviews some of the more recent knowledge about the problem, with particular reference to medical implications. The incidence and distribution of the problem and the relative importance of the medical examination are reviewed, and the diagnostic significance of clinical presentations such as vulvovaginitis, recurrent urinary tract infection and masturbation is evaluated. The agents responsible for sexually transmitted diseases in abused children are reviewed. Many crucial psychosocial issues are raised in the evaluation and management of sexual abuse. The author discusses some aspects of abuse that are hard to confront, such as the possible pleasure of the child and the nonoffending role of the mother in cases of incest. Information from sources other than the medical literature on the characteristics of abusers, therapy and prevention is reviewed. The medical implications of the Badgley Report are also discussed.